2000
DOI: 10.2460/ajvr.2000.61.1501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of administration of nonsteroidal anti-inflammatory drugs before surgery on renal function in clinically normal dogs

Abstract: In clinically normal dogs undergoing general anesthesia and elective surgery, the use of NSAID as analgesics is not contraindicated. Compared with ketorolac or ketoprofen, carprofen had the least effect on renal function and integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 23 publications
5
33
0
1
Order By: Relevance
“…A previous study of ketoprofenassociated adverse renal effects found decreased endogenous creatinine clearance in dogs receiving ketoprofen before castration surgery [8]. Likewise, a separate study [22] reported decreased FC Na and urine specific gravity, and increased renal tubular epithelial cells in urine sediment after ovariohysterectomies in dogs receiving ketoprofen before surgery. Even short-term administration of ketoprofen may carry the risk of adverse renal effects under inhalation anesthesia.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study of ketoprofenassociated adverse renal effects found decreased endogenous creatinine clearance in dogs receiving ketoprofen before castration surgery [8]. Likewise, a separate study [22] reported decreased FC Na and urine specific gravity, and increased renal tubular epithelial cells in urine sediment after ovariohysterectomies in dogs receiving ketoprofen before surgery. Even short-term administration of ketoprofen may carry the risk of adverse renal effects under inhalation anesthesia.…”
Section: Discussionmentioning
confidence: 94%
“…Opioid analgesics have traditionally been the most widely used analgesics in veterinary practice 31 . The classification of opioid analgesics as controlled drugs, concerns regarding their adverse effects and lack of familiarity with opioids available make veterinarians reluctant to use them for pre-emptive analgesia 6,23 . Moreover, opioids are known to cause cardiopulmonary depression and increase depth of sedation and thus prolong recovery, which can, depending on practice circumstances, be interpreted as undesirable effects of opioid use 20,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Its increased activity in urine has been associated with proximal tubular damage in dogs (Heiene et al 1991). Excretion of urinary alkaline phosphatase is used to evaluate renal function in different conditions (Lobetti and Joubert 2000;Lobetti and Lambrechts 2000;Heiene et al 2001;Raekallio et al 2006). …”
Section: Alkaline Phosphatasementioning
confidence: 99%